(untitled) (International Journal of Engineering and Computer Science, 2019)
The paper describes an industrial business study carried out to regain the business knowledge embedded in a legacy COBOL application. The aim of this work was to extract out the information required to re- implement the Legacy programs in a new client/server environment. The progress solution is in four step. Firstly, the programs were restructured, secondly the programs were sliced into business logic modules, third the business modules were subjected to a multi view analysis and finally the views were integrated into a unified documentation describing the data, decision and procedural flow of each program slice.